Macroeconomic Policies in a Low Interest Rate Environment: Back to Keynes?. (1st March 2018) - Castelnuovo, Efrem; Lim, Guay; Pellegrino, Giovanni
ABSTRACT: This article discusses macroeconomic policies in a low interest rate environment, the central theme of the 2017 edition of the Melbourne Institute Macroeconomic Policy Meeting. After reviewing possible causes of the decline in interest rates observed since the 1990s, we present and discuss some of the challenges that monetary and fiscal policy face in a 'new normal' environment characterised by a real natural interest rate close to zero. Proposals by leading researchers on how to operate in such an environment are presented and discussed. We conclude by outlining some research questions that are highly relevant from a policy perspective.